Microfinance Institutions and Empowerment of Women in Rural Area: A Case in Tangerang - Mukhaer Pakkana; Lincolin Arsyad (Signifikan: Jurnal Ilmu Ekonomi, 2017)
The purpose of this study is to discover the performance of the financial independence, the members’ welfare, and accessibility of microfinance institutions to the rural areas in the Tangerang District. To measure the financial dependence is using financial ratios. Measuring levels of performance of the members’ welfare and accessibility using Chi-Square. The results found that, first, the level of welfare of members. The coastal areas have a higher loan value than other regions. Expenditure and income of members, industrial areas have high levels of spending and revenues higher than other regions. The performance of a range to members based on a group basis. Second, the performance of financial independence, categorized as "Healthy". The coastal area is 86.40, the area around the industrial area is 85.71 and agricultural area is 83,73. Third, the level of non-performing loans, the coastal area is 0.03, the industrial area is 0,26, and the agricultural area is 0.19.DOI:  10.15408/sjie.v6i1.4637